Impact of Acute and Chronic Stressors on the Morphofunctional Characteristics of Long Bones in Spontaneously Hypertensive Rats: A Pilot Study Using Histological and Microtomographic Analysis - Marina Ribeiro Paulini; Dimitrius Leonardo Pitol; Sara Feldman; Camila Aparecida Ribeiro; Daniela Vieira Buchaim; Rogerio Leone Buchaim; João Paulo Mardegan Issa (Biomedicines)
Background/Objectives: Hypertension is a major contributor to cardiovascular diseases and is often intensified by psychological stress, which can also affect bone metabolism. Although both conditions independently compromise bone health, their combined impact—particularly under acute and chronic stress—remains unclear. This pilot study aimed to assess the effects of such stressors on bone structure in spontaneously hypertensive rats (SHRs). Methods: Forty male rats, both normotensive and SHRs, were randomly assigned to control, acute stress, or chronic stress groups. Acute stress involves a single 2 h physical restraint. Chronic stress was induced over 10 days using alternating stressors: agitation, forced swimming, physical restraint, cold exposure, and water deprivation. Tibial bones were analyzed by microcomputed tomography (micro-CT), and histology was performed using Hematoxylin and Eosin and Masson’s Trichrome stains. Results: Micro-CT showed increased trabecular bone volume in normotensive rats under chronic stress, whereas SHRs displayed impaired remodeling under both stress types. Histological analysis revealed preserved connective tissue overall but evident changes in growth plate structure among stressed rats. SHRs exhibited exacerbated trabecular formation and cartilage abnormalities, including necrotic zones. Conclusions: Both acute and chronic stress, especially in the context of hypertension, negatively affect bone remodeling and maturation. Despite the absence of overt inflammation, structural bone changes were evident, indicating potential long-term risks. These findings highlight the importance of further studies on stress–hypertension interactions in bone health as well as the exploration of therapeutic approaches to mitigate skeletal damage under such conditions.